2-D Physical Modeling to Measure the Effectiveness of Perforated Skirt Breakwater for Short-Period Waves - Ajiwibowo, Harman (ITB Journal Publisher, LPPM ITB, 2011)
The effectiveness of a breakwater can be measured by quantifying the transmission coefficient (KT). The smaller the coefficient, the better the performance of the breakwater. A physical modeling on the proposed breakwater was conducted to identify the coefficient of Perforated Skirt Breakwater (PSB). The PSB model was tested in 2-D wave flume at Ocean Wave Research Laboratory FTSL ITB, to obtain the effectiveness of PSB for short-period waves (prototype periods, Tp= 4 second and smaller). The scaling of PSB models applies the principle of Froude Similarity, where the Froude number in model equals to the Froude number in prototype (Frm=Frp). The flume is equipped with 5 resistance-type wave probes and 8-channel DAS (Data Acquisition System). Wave heights (H) and wave periods (T) data were observed both manually by visual observation and wave probes readings (processed later with method of âzero mean up-crossingâ technique). The incoming wave heights (Hi) and transmitted wave heights (Ht) were measured and processed to obtain the transmission coefficient (KT). The relationships between KT and non-dimensional variables (skirt draft / incident wave height, S/Hi) are analyzed and the calculated effectiveness of the PSB for varied environmental condition is obtained to be up to 70%.